Practical classes as a teaching strategy for topics in plant biology for high school students: a case study with beans and corn (Research, Society and Development, 2022)
The use of practical classes has great potential helping us in the teaching and learning process in plant biology content, in addition to providing the student with a leading role through active methodologies. In order to signify learning for this content, five practical classes were applied to a total of 38 students, from two different classes of the second year of high school in the public network of Paraíba. Questionnaires, participant observation and notes made by students during the practical classes were used for data collection. During the interventions, it was observed the student protagonism reflected in the active participation during the conduction of the practical classes. In the analysis of the tests, the progression of knowledge learned at the end of the interventions was noticeable. The students, when willing to participate, showed great protagonism during the execution of the activities, which contributed to an active and lasting learning proven through diagnostic evaluation and concept maps. Thus, it is expected that the stimulus to practical activities will positively interfere with learning, even for other subjects.